Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4103/ccd.ccd_1117_16
|View full text |Cite
|
Sign up to set email alerts
|

A novel conservative approach combining “SealBio” and “Surgical Fenestration” for healing of large periapical cystic lesions of endodontic origin: A pilot study

Abstract: Objectives:To evaluate the treatment outcome of large periapical cystic lesions treated by combining two novel, conservative approaches, “SealBio” and “Surgical Fenestration”.Materials and Methods:Five cases (4M:1F, age range 14-38 years, mean age 24.5 years) of large periapical cystic lesions, diagnosed on clinical and radiographic examination, were included in the study. After informed consent, endodontic treatment was initiated; chemo-mechanical preparation and intra-canal dressing of calcium hydroxide was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…This result followed a similar concept presented by Holland et al [ 27 ], who showed the significance of root canal obturation in the repair of the surrounding regions. Moreover, this concept is in line with the ideas expressed by Shah [ 28 ] and Jha et al [ 29 ], whose studies exhibited the importance of biomechanical preparation of the radicular system and the application of an intracanal medication in achieving successful outcomes of endodontic treatments.…”
Section: Discussionsupporting
confidence: 81%
“…This result followed a similar concept presented by Holland et al [ 27 ], who showed the significance of root canal obturation in the repair of the surrounding regions. Moreover, this concept is in line with the ideas expressed by Shah [ 28 ] and Jha et al [ 29 ], whose studies exhibited the importance of biomechanical preparation of the radicular system and the application of an intracanal medication in achieving successful outcomes of endodontic treatments.…”
Section: Discussionsupporting
confidence: 81%